2021
DOI: 10.3389/fcvm.2021.707454
|View full text |Cite
|
Sign up to set email alerts
|

Agreement Between Invasive Wire-Based and Angiography-Based Vessel Fractional Flow Reserve Assessment on Intermediate Coronary Stenoses

Abstract: Background: Angiography-based functional assessment of coronary stenoses emerges as a novel approach to assess coronary physiology. We sought to investigate the agreement between invasive coronary wire-based fractional flow reserve (FFR), resting full-cycle ratio (RFR), and angiography-based vessel FFR (vFFR) for the functional assessment of coronary stenoses in patients with coronary artery disease.Materials and Methods: Between Jan 01, 2018, and Dec 31, 2020, 298 patients with 385 intermediate lesions receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
3
1
0
Order By: Relevance
“…More importantly, among the patients with more severe coronary stenosis, we demonstrated a high diagnostic performance of vFFR. Consistent with previous findings, 5,6,14 our results suggested that vFFR is a clinically feasible alternative to FFR, even in patients with such functionally severe coronary stenosis. In addition, to the best of our knowledge, our study is the first to demonstrate similar diagnostic performance between vFFR and NHPRs for coronary stenosis as evaluated by FFR.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…More importantly, among the patients with more severe coronary stenosis, we demonstrated a high diagnostic performance of vFFR. Consistent with previous findings, 5,6,14 our results suggested that vFFR is a clinically feasible alternative to FFR, even in patients with such functionally severe coronary stenosis. In addition, to the best of our knowledge, our study is the first to demonstrate similar diagnostic performance between vFFR and NHPRs for coronary stenosis as evaluated by FFR.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, to the best of our knowledge, our study is the first to demonstrate similar diagnostic performance between vFFR and NHPRs for coronary stenosis as evaluated by FFR. Previous reports also demonstrated good agreement between FFR and NHPRs, irrespective of coronary artery phenotypes (i.e., stable coronary artery and acute myocardial infarction), 14,15 which may support our findings emphasizing the significance and feasibility of evaluating coronary stenosis based on vFFR.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The pressure wire–derived FFR became widely used after that, owing to its independence from the baseline flow and relative simplicity and cost-effectiveness for treatment decision-making compared with ICA [ 35 - 37 ]. However, some have suggested the higher [ 38 ] or comparable [ 39 ] diagnostic accuracy of ICA-FFR, compared with wire-based, which unnecessarily imposes the patients to the wire pressure. In this method, coronary stenosis is measured by the reduction of perfusion pressure induced by the viscous and expansion losses of the narrowed vessel, calculated by the Poiseuille’s law and Bernoulli’s equation, and reported by the fraction from the normal value of 1.0 in every patient and every vessel [ 40 ].…”
Section: Invasive Coronary Angiography Derived Fractional Flow Reserv...mentioning
confidence: 99%